Pengawasan Badan Permusyawaratan Desa terhadap Tata Kelola Keuangan Desa, di Desa Hadakewa Kecamatan Lebatukan Kabupaten Lembata - Clarentin Putri Paun; Yohanes G. Tubahelan; Yohanes Tuan (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this research is to analyze the supervision of the village consultative body on village financial governance, in Hadakewa Village, Lebatukan District, Lembata Regency. This research uses empirical legal research methods sourced from data obtained directly in the form of opinions from respondents, namely the Village Head, Village Secretary, Village Finance Clerk, Community Leaders, Hadakewa Village Consultative Body. The results showed that (1) the accountability of the Hadakewa village government regarding the management of village funds has a form of transparency with the village fund realization report. This report is not only submitted to the district / city government but also to the community and the Village Consultative Body which acts as a supervisor of the use of the Village Fund. Thus, this action reflects the Village's commitment to implementing the principles of accountability and transparency in the management of the Village Fund (2) shows that the implementation of financial governance supervision based on management principles is running well and all reports on the use of village funds are carefully recorded and reported from village officials to the Village Consultative Body.